1989
DOI: 10.1021/bi00435a032
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of dopamine .beta.-hydroxylase by .beta.-ethynyltyramine: kinetic characterization and covalent modification of an active site peptide

Abstract: beta-Ethynyltyramine has been shown to be a potent, mechanism-based inhibitor of dopamine beta-hydroxylase (DBH). This is evidenced by pseudo-first-order, time-dependent inactivation of enzyme, a dependence of inactivation on the presence of ascorbate and oxygen cosubstrates, the ability of tyramine (substrate) and 1-(3,5-difluoro-4-hydroxybenzyl)imidazole-2-thione (competitive multisubstrate inhibitor) to protect against inactivation, and a high affinity of beta-ethynyltyramine for enzyme. Inactivation of DBH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…This idea is supported by the location of all 3 modified residues within the putative catalytic domain described above. Characterisation of the attachment site peptides [4,5] together with extensive partial sequence data (unpublished observations) indicate approximately 95°7o sequence identity between human and bovine DBH throughout this domain. Several consensus features in this section of the PAM sequences from 3 species are also present in DBH ( fig.3).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…This idea is supported by the location of all 3 modified residues within the putative catalytic domain described above. Characterisation of the attachment site peptides [4,5] together with extensive partial sequence data (unpublished observations) indicate approximately 95°7o sequence identity between human and bovine DBH throughout this domain. Several consensus features in this section of the PAM sequences from 3 species are also present in DBH ( fig.3).…”
Section: Discussionmentioning
confidence: 87%
“…Independent evidence for an extended catalytic domain in DBH comes from attachment sites of mechanism-based inhibitors. Three of these have recently been identified, Tyr 216 [4] and Tyr 357 for p-cresol (unpublished results) and His 398 for fl-ethinyltyramine [5]. The chemistry of inactivation for these compounds indicates that covalent incorporation should be restricted to the vicinity of the active site.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…DeWolf et al (1988,1989) have reported the isolation of two bovine DBH tryptic peptides which are labelled by substrate analogs-APDVLIPGZZTT-YWCYVTELPDGFPR, labelled by p-cresol , and CTQLALPASGIHIFASQLHTH-LTGR, labelled by P-ethinyltyramine (DeWolf et al, 1989). These peptides are contained within the bovine DBH primary structure (Figs.…”
Section: O P G D V L I T S C T Y N T E D R R L a T V G G F G I L E E mentioning
confidence: 99%